REFORMULASI HUKUM TALAK DI LUAR PENGADILAN - Syari, Makmun (IAIN Samarinda, 2015)
Based on the Qur’an and the Hadith, ulama agree that talaq divorce has been prescribed in Islam. The talaq divorce, however, is used as the last resort of discord between a men and his wife in a household that can no longer be maintained or even bring harm to the couple. This article discusses the concept of talaq divorce in Islam. It especially analyses the current practice of talaq divorce in the Indonesian legal system, i.e. by requiring its pronouncement before the Religious Court (Pengadilan Agama) so as to be effectual. Even though this is a novel practice in Islamic law, its application is justifiable in order to prevent arbitrary talaq divorce pronounced by a man as well as to give legal protection and maintenance to a divorced wife and her children after the pronouncement of talaq.